Estereótipos de gênero na educação física nos anos iniciais em Humaitá-AM - Silva, Diego Maciel da (Brasil, 2022)
This Course Completion Work (TCC) comes from a research project with the Institutional Program for Scientific Initiation Scholarships (PIBIC), developed between August 2021 and August 2022, at the Federal University of Amazonas (UFAM) , Institute of Education, Agriculture and Environment (IEAA). Still, such work had already been of interest during the training process in the Pedagogy course, started by the author of this work in the second half of 2017. At school, beliefs and expectations about sexual binarisms can constitute gender stereotypes, standardizing men and women. These social beings learn in different social educational institutions the acceptable social standards of how they should behave, dress, etc., in accordance with the expectations of their gender. Starting from an unrestricted view regarding its post-critical methodological approach, the present research is classified as qualitative regarding the analysis of its problem and a study classified as descriptive regarding its objectives. Regarding the technical elements of the study, bibliographic research, the questionnaire and observation at school were used. In this sense, the present research had as general objective to analyze if there are gender stereotypes in the practical activities of Physical Education in the 5th year of Elementary School in Humaitá/AM. Its problem sought to answer how gender stereotypes can be re/produced in the practical activities of Physical Education in the 5th year of Elementary School. Based on the results, the present study reveals that the occurrence of the manifestation of gender stereotypes in the discipline of physical education occurs, more explicitly, in practical (physical) activities arising from the sport content. Held on the school's court, this activity shows that in the soccer sport (at school, futsal) students/boys demonstrate discriminatory behavior based on gender.